(3GdPNjQI aj Yde GdWHs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3Cbhd GPG cGf eHOC chffG MSH eG bGdg LGdjfhS ai cJGHg aj JOHjQ GdCUMGA ef GdOe hGdeSfj s
(3BNQgG (B:s
(3hjYLf HYTQI eKGbjd eSc hjMeO CjGe Ke jbQU hjLaa aj GdXd ? s
(3GdfSNI HgG MhGTs
(3jMJhi Ydi GKfjf hKdGKjf ebGdI WHjIs
(3hdcf JfJgi GdfSNI efP BNQ GdebGdI GdSGOSI hGdYTQhf HYde eNGda bOQ (B10 (3GSWQ s
(3jMJhi Ydi agQS aj ChdI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
Keywords: (3eJaQbGJs